Cradle to cradle remaking the way we make things - McDonough, William (New York Tantor, 2008)
"Reduce, reuse, recycle" urge environmentalists; in other words, do more with less in order to minimize damage. As William McDonough and Michael Braungart argue in their provocative, visionary book, however, this approach perpetuates a one-way, "cradle to grave" manufacturing model that dates to the Industrial Revolution and casts off as much as 90 percent of the materials it uses as waste, much of it toxic. Why not challenge the notion that human industry must inevitably damage the natural world, they ask.
Unabridged
Keywords: Recycling (Waste, etc.)